The Cytoprotective and Cell Recovery Properties of Apple Extracts on H2O2 induced-NIH3T3 Cells: An Anti Aging Candidate - Nunuk Aries Nurulita; Anjar Mahardian Kusuma; Darsini Darsini; Weny Delvia; Veby Tri Yulianti (Indonesian Journal of Cancer Chemoprevention, 2018)
Apple contains high concentration of phenolic compounds that protect cells from oxidative stress. The prolong exposure of free radicals may induce cell damage and premature cell aging. Both local and imported apple contain flavonoid, saponin, tannin, steroid, and terpenoid. The extract of local and imported apples showed low toxicity on NIH3T3 fibroblast cells, with IC50 value of 529 and 463 µg/mL, respectively. Both apple extracts (50 – 250 µg /mL) protected three-day-H2O2 induced-cell damage and cell death. Protective effect was observed as the viability increase of treated cells compared to untreated ones. The protective effect of both extracts were higher than the effect of vitamin C as standard antioxidant at this study. Both apple extracts could reverse cell damage caused by three-hour-high concentration H2O2 exposure, similar with vitamin C. Low concentration of both extracts (50 µg /mL) induced the increase of fibroblast cells’ proliferation kinetics. The extract of imported apple showed higher properties of protective, cell recovery and proliferation of fibroblast cells tha local apple, but not statistically significance. This study concludes that the extract of local and imported apples have high potency in cytoprotective effect and cell recovery of damaged cells caused by free radicals induction. Both apple extracts have high potency to be developed the candidate of antiaging and cells’ regeneration agent.Keywords : antiaging, cell recovery, cytoprotective, NIH3T3 cells